Innovation platforms: a tool to enhance small-scale farmer potential through co-creation. Issue 8 (17th November 2018) - Sell, Mila; Vihinen, Hilkka; Gabiso, Galfato; Lindström, Kristina
ABSTRACT: This article describes the process and analyses the results of a project in Ethiopia establishing an innovation platform (IP) as a tool for co-creation from an innovation systems perspective. The results are encouraging, suggesting positive effects both on yields, but more importantly on the capacity and role of participants as communicators and agents of change in the community. The IP seems promising in creating new networks and modes of communication. The importance of good facilitation, commitment by all members from the start, and feedback loops driving the process was found to be essential.